Cholecystokinin facilitates the formation of long-term heterosynaptic plasticity in the distal subiculum - Fengwen Huang; Abdul Baset; Stephen Temitayo Bello; Xi Chen; Jufang He (Communications Biology)
Abstract It has been well established that Cornu Ammonis-(CA1) and subiculum (SUB) serve as the major output components of the entorhinal-hippocampal circuitry. Nevertheless, how the neuromodulators regulate the neurocircuitry in hippocampal formation has remained elusive. Cholecystokinin (CCK), is the most abundant neuropeptide in the central nervous system, which broadly regulates the animal’s physiological status at multiple levels, including neuroplasticity and its behavioral consequences. Here, we uncover that exogenous CCK potentiates the excitatory synaptic transmission in the CA1-SUB projections via CCK-B receptor. Dual-color light theta burst stimulation elicits heterosynaptic long-term potentiation in distal SUB region. Light activation of medial entorhinal cortex (MEC) derived CCK-positive neurons triggers the CCK release in the SUB. Neuronal activities of SUB-projecting MECCCK neurons are necessary for conveying and processing of navigation-related information. In conclusion, our findings prove a crucial role of CCK in regulating neurobiological functions in the SUB region.